Penerapan Pembelajaran Kooperatif Melalui Model Group Investigation Untuk Meningkatkan Literasi Ekonomi Siswa - Dadang Saepuloh; Siti Rodiah (Jurnal Pendidikan Ekonomi, 2020)
This research was motivated by the problems in the low economic literacy of students in economic subjects are supported by still lack of economic literacy of students based on the results of observations. This research aims to reveal the differences in increasing economic literacy of students before being given treatment and after treatment is given through a learning models of Group Investigation (GI) experimental class and conventional learning (lectures) control class. This research is a quantitative research using Quasi-Experimental Design. Economic literacy Data Obtained from the post-test students in the form of essays, Reviews These results indicate that there is a difference between economic literacy of students who applied to the learning model of group investigation with the economic literacy of students who applied to conventional models. Based on the research results using t-test. this matterit can be concluded that the Group Investigation learning models can improve economic literacy.DOI: https://dx.doi.org/10.17977/um014v13i12020p030